Sudut Pandang Etika Profetik Terhadap Khazanah Percopetan Dalam Film Preman Pensiun - Robingun Suyud El Syam; Alfan Nurngain; Salis Irvan Fuadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article aims to convey a prophetic ethical perspective on the treasures of pickpocketing in the film Preman Pensiun, starting from the neglected irony. This paper uses qualitative literature research, analyzed inductively using Kuntowijoyo's theory of prophetic ethics. The research results show that pickpocketing is an action that is contrary to the ethical values of humanization, because it contains elements of dependency, cruelty and causes hatred from other parties. The act of pickpocketing shows a person's lack of resistance to injustice, where the spirit of liberation has disappeared in him. Transcendence ethics requires people to develop a dimension of awareness within themselves that whatever they do is judged by God, and everything will be accounted for. Research implications for similar research in order to explore it philosophically, in a broader scope. Research contributes to the meaning of a film from the aspect of prophetic ethics.